2019
DOI: 10.1080/21645698.2019.1680078
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic crops for the agricultural improvement in Pakistan: a perspective of environmental stresses and the current status of genetically modified crops

Abstract: Transgenic technologies have emerged as a powerful tool for crop improvement in terms of yield, quality, and quantity in many countries of the world. However, concerns also exist about the possible risks involved in transgenic crop cultivation. In this review, literature is analyzed to gauge the real intensity of the issues caused by environmental stresses in Pakistan. In addition, the research work on genetically modified organisms (GMOs) development and their performance is analyzed to serve as a guide for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 175 publications
0
12
0
Order By: Relevance
“…The global production of genetically modified crops has grown profoundly from 1.7 million hectares in 1996 to 191.7 million hectares in 2018 (Babar et al 2019). The agriculture practices with commercial transgenic crops, such as cotton (a leading cash crop) and maize (Trivedi et al 2012), have brought enormous economic benefits worldwide (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The global production of genetically modified crops has grown profoundly from 1.7 million hectares in 1996 to 191.7 million hectares in 2018 (Babar et al 2019). The agriculture practices with commercial transgenic crops, such as cotton (a leading cash crop) and maize (Trivedi et al 2012), have brought enormous economic benefits worldwide (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have found that the expression of the exogenous Bt protein in insect-resistant transgenic rice under salinity, P deficiency, K deficiency, and other adverse conditions, were significantly lower than under no-stress control conditions. 18 , 24 , 25 The negative correlation between Bt protein expression and stress has also been reported in insect–resistant transgenic cotton and maize. 26–30 Taken together, these findings indicated that environmental stress limited the expression of exogenous proteins in insect-resistant transgenic crops; however, these proteins were still expressed in varying degrees.…”
Section: Expression Of the Exogenous Protein Cry1c* Under Four Growing Conditionsmentioning
confidence: 93%
“…On July 20 (at tillering), August 5 (at jointing), September 5 (at heading), September 25 (at filling) and October 25 (at maturing), leaves and stems of five plants were sampled and mixed into one duplicate sample in each plot and five such duplicate pots from each treatment were stored at −80°C for determination of Cry1C* protein content by the enzyme-linked immunosorbent assay kit (EnviroLogix Inc, Portland, ME, USA). The detailed analytical procedure was carried out according to Fu et al 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from the World Resources Institute concluded that “the case for using [genetic engineering] is compelling when the full range of potential gains and costs is taken into consideration” (Searchinger et al, 2019). Nonetheless, public perception of GM crops remains poor in many countries, with limited scientific understanding amongst many of the public and the perception that GM crops are “unnatural” and therefore unsafe (Babar et al., 2020; McFadden & Smyth, 2019; McPhetres, Rutjens, Weinstein, & Brisson, 2019). Interestingly, conventional breeding in sweet potato has selected for genes introduced to the species by Agrobacterium in the wild (Kyndt et al., 2015), similarly to the way GM is performed in the laboratory, and overall, the evidence clearly suggests that the risk to the environment of a new variety should be considered primarily in light of its phenotype and not in the methodological approach used to produce it (National Academies of Sciences Engineering Medicine, 2016).…”
Section: Future Developmentsmentioning
confidence: 99%